Zemstvos of Ukrainian provinces in the late 19th – early 20th centuries in the context of the formation of civil society in Ukraine - Saraieva, Olha (Young Scholars Grinchenko – Seton International Journal, 2025)
Today, various aspects of the emergence and functioning of civil society have become the subject of detailed study. The relevance of this issue is underscored by the fact that many states, including Ukraine, are undergoing a political transformation from authoritarian to democratic political systems. Local self-government bodies occupy a special place among the institutions that constitute civil society. As a micro-model of civil society, local self-government makes it possible to understand the patterns and contradictions in its development. The involvement of broad population segments in addressing regional issues contributes to individuals’ awareness of civic responsibility, tolerance, and an active civic stance. A society that has mastered the practice of self-governance can develop mechanisms for public oversight of power, realizing the idea of social justice, and ensuring social protection. The level of development of local self-government bodies serves as an indicator of the extent of civil initiatives and the maturity of society. Ukraine has considerable experience in the functioning of local self-government and its development through the advancement of civil society. These very aspects are the focus of this article.